组合行星齿轮箱动态特性研究 - 杨兵; 邓绪山; 刘增民 (Jixie chuandong)
The dynamic equations of a compound planet gear trains are established.The random gear errors and mesh stiffness are considered in the equations.The inherent characteristics of the system are got,as well as the load sharing coefficient,dynamic load coefficient and so on.